Web 2.0 Business Models Taxonomy and its Relation with Web 2.0 Features - ali Masoumi Lari; monireh Hosseini (Journal of Information Technology Management)
Web 2.0 is not a single technology or standard but rather a set of concepts and features. Web 2.0 concepts and features call for further attention. Since, previous studies have only addressed only some of these concepts and features. In order to give a comprehensive view of Web 2.0, these features are collected through literature review and a framework of Web 2.0 features is presented. Also, due to the lack of an integrated and comprehensive classification of Web 2.0 business models and the diversity of approaches and the incompleteness of the models, this study has investigated, compared and integrated previous models and classifications using the meta-synthesis method. In this study, a new classification of Web 2.0 business models has been presented and the conceptual relationship between the characteristics of Web 2.0 and Web 2.0 business models has been proposed and the most important features of each business model have been mentioned. Finally, real examples from Iranian and international sites for each model has been presented through observation and evaluation of websites or from past research.